Fatal Rhinofacial Mycosis Due to Aspergillus nomiae: Case Report and Review of Published Literature - Zhou, Ya Bin; Li, Dong Ming; Houbraken, Jos; Sun, Ting Ting; de Hoog, G. Sybren (Frontiers in Microbiology, 2020)
Summary Background: A 73-year-old female suffering from acute myeloid leukemia presented with progressive rhinofacial mycosis. Suspecting it as a mucormycosis, the antifungal amphotericin B was administered empirically, but the patient did not respond as planned. The fungus was then isolated from the biopsied tissue and morphologically idenfied as a species of Aspergillus. Necrosis progressed and she died of cerebral hemorrhage. Since A. flavus has susceptibility to amphotericin B, and several other Aspergillus species can be misidentified as A. flavus, the observed resistance necessitated a re-examination of the fungal isolate. Methods: The fungal strain was re-isolated and re-examined morphologically. Additionally, genomic DNA was extracted from the fungus and sequences were obtained from three genomic regions (the rDNA internal transcribed spacer region, and portions of the β-tubulin and calmodulin genes) to more accurately identify this Aspergillus strain. Its antifungal susceptibility was assessed using multiple compounds and our findings were compared with literature data. Results: The fungal culture again yielded an Aspergillus isolate morphologically identical to Aspergillus flavus. Molecular analyses, however, revealed the strain to be A. nomiae, a close relative of A. flavus in section Flavi, and it exhibited resistance to amphotericin B. Reviewing the literature, only five other cases of A. nomiae infection in humans have been reported worldwide. Conclusion and clinical importance: The rhinofacial mycosis of patient was actually due to A. nomiae. The initial misidentification of the fungus, coupled with its resistance to amphotericin B, could be the reason treatment did not help the patient in question. We postulate that clinical A. nomius infections may be underreported and that accurate and speedy pathogen identification are important so that an effective antifungal regimen can be administered.